Musculoskeletal Diseases 2017-2020 : diagnostic imaging : 49th International Diagnostic Course in Davos (IDKD), Davos, March 26-30, 2017 ; including the Nuclear Medicine Satellite Course "Diamond" Davos, March 25-26, 2017, Pediatric Radiology Satellite Course "Kangaroo" Davos, March 25, 2017, Breast Imaging Satellite Course "Pearl" Davos, March 25, 2017 and additional IDKD Courses 2017-2020 /: diagnostic imaging : 49th International Diagnostic Course in Davos (IDKD), Davos, March 26-30, 2017 ; including the Nuclear Medicine Satellite Course "Diamond" Davos, March 25-26, 2017, Pediatric Radiology Satellite Course "Kangaroo" Davos, March 25, 2017, Breast Imaging Satellite Course "Pearl" Davos, March 25, 2017 and additional IDKD Courses 2017-2020. (2017) - Unknown
No abstract available